Characteristics of RS3 Starch Gembolo (Dioscorea bulbifera bulbils) with Several Autoclaving-Cooling Cycles - Fatimah, Siti; Triwitono, Priyanto; Saputra, Wahyu Dwi (Indonesian Food and Nutrition Progress, 2026)
Gembolo (Dioscorea bulbifera bulbils) is a tuber that can be used as an alternative carbohydrate source. This tuber contains various essential minerals and vitamins; it also has a starch content of 6.627% and an amylose content of 30.63%. Research into gembolo has been limited to its physical and chemical characterization and its nutritional content. Using gembolo starch as a source of type RS3 via the autoclaving-cooling method has not yet been studied. RS3 promotes digestive and metabolic health by functioning as a type of fiber. Using gembolo starch as a source of type RS3 via the autoclaving-cooling method has not yet been studied. RS3 promotes digesti ve and metabolic health by functioning as a type of fiber. The cycle frequency used consisted of 1 to 5 autoclaving-cooling cycles. The analysis of the physicochemical properties included the following: RS, starch, amylose, amylopectin, water content, granule morphology, pasting properties, and water-holding capacity (WHC) and oil-holding capacity (OHC). After modification of gembolo starch with 1-5 autoclaving-cooling cycles, there was a 4.49% decrease in water content and a 9.65% decrease in starch content. There was also a 8.56% decrease in amylose content and a 33.29% increase in RS content. An increase in WHC of 144.22%, an increase in OHC of 2.91%, and a decrease in the pasting profile of 7753 cP. Based on these data, the treatment of 5 autoclaving-cooling cycles produced the highest RS of 74%. From this research, gembolo can be a potential source of functional RS3 starch.